2019
DOI: 10.1002/jcp.28466
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Aloe vera against cartap‐ and malathion‐induced toxicity in Wistar rats

Abstract: Exposure to mixture of pesticides in agricultural practices pose a serious threat to the nontarget animals. In present work, we have evaluated the synergistic effect of cartap and malathion on rat liver followed by impact of Aloe vera leaves aqueous extract, which is not known. The animals in eight groups were used; each containing six rats: Group 1 acted as a control, Group 2—control with A. vera leaves aqueous extract, Group 3—with cartap, Group 4—with malathion, Group 5—with mixture of cartap and malathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 85 publications
11
39
0
Order By: Relevance
“…The data from the present study reflected substantial variations in the body weights of rats exposed to pesticides, which may be associated to the cholinergic deficiency and oxidative stress. Our findings supported the results presented by others [ 37 , 38 ]. However, the pretreatment of rats by A. vera leaf extract markedly attenuated changes in body weight of animals exposed to pesticides.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The data from the present study reflected substantial variations in the body weights of rats exposed to pesticides, which may be associated to the cholinergic deficiency and oxidative stress. Our findings supported the results presented by others [ 37 , 38 ]. However, the pretreatment of rats by A. vera leaf extract markedly attenuated changes in body weight of animals exposed to pesticides.…”
Section: Discussionsupporting
confidence: 94%
“…The toxicity of OPs has been verified by other workers who have shown rise in the activities of AST, ALT, ACP, and ALP [ 39 ]. The reports from other authors also indicated similar observations [ 38 , 63 ]. The transaminases are recognized to play vital roles in regulating physiological processes, catalyzing trans-amination reactions to facilitate the metabolism of xenobiotics and other macromolecules [ 64 ].…”
Section: Discussionsupporting
confidence: 83%
“…Several plant extracts [ 49–51 ] are known to have antioxidant properties against oxidative stress in different organs and xenobiotics. [ 52–56 ] The results showed that lipid peroxidation and MDA level in the spinal cord tissue increased in Cup group and EA 100 mg/kg co‐treatment with Cup reversed this undesirable alteration compare with Cup group. Increased ROS production, oxidative phosphorylation dysfunction, and calcium hemostasis imbalance and decreased antioxidant defense system in serum and cerebrospinal fluid were reported in MS disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mohammadzadeh and his colleagues found that crocin, saffron active components, exhibited protective effects against MAL-induced Parkinson-like behavior through reducing lipid peroxidation, improving motor deficits and anti-inflammatory effects (Mohammadzadeh et al 2018). Other natural products that approved efficacy include aged garlic extract (Ramadan et al 2017), grape seed extract (Abdel-Salam et al 2018), Aloe vera (Gupta et al 2019), caffeic acid (Rezg et al 2015), thymoquinone (Abdel-Daim et al 2020), and curcumin (Alp et al 2012). Recommendations for increasing the use of these antioxidants on a daily basis, especially those working in pesticides' factories or agriculture, may be warranted.…”
Section: Novel Treatments For Mal Poisoningmentioning
confidence: 99%